2004
DOI: 10.1186/1476-511x-3-24
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Conjugated fatty acid, the general term of positional and geometric isomers of polyunsaturated fatty acids with conjugated double bonds, has attracted considerable attention because of its potentially beneficial biological effects. In the present study, dietary effect of pomegranate seed oil rich in punicic acid (9cis, 11trans, 13cis-conjugated linolenic acid; 9c, 11t, 13c-CLNA) on lipid metabolism was investigated in obese, hyperlipidemic Otsuka Long-Evans Tokushima Fatty (OLETF) rats. After 2 weeks feeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 45 publications
(35 reference statements)
4
47
0
Order By: Relevance
“…In conclusion, certain fatty acids such as conjugated linoleic acid and conjugated trienoic acids were shown to inhibit SCD [16, 17]. As known, marigold contains naturally occurring conjugated triene fatty acid, calendic acid, to be believed to inhibit the enzyme stearoyl-CoA desaturase.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, certain fatty acids such as conjugated linoleic acid and conjugated trienoic acids were shown to inhibit SCD [16, 17]. As known, marigold contains naturally occurring conjugated triene fatty acid, calendic acid, to be believed to inhibit the enzyme stearoyl-CoA desaturase.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies indicated that given to rats in the triglyceride form, punicic acid was well absorbed, metabolized and stored in rat tissues [39], [46], [63], [64]. Pomegranate seed oil provided protection against TNBS-induced ulcerations and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pomegranate flower extracts seem to effectively improve diabetes and were reported to decrease blood total cholesterol, triglyceride, LDL‐C, VLDL‐C, and increase HDL‐C in streptozotocin (STZ)‐induced diabetic rats . However, although pomegranate seed extract caused no obvious improvement in dyslipidemia in T2DM, administration of 1% pomegranate seed oil, which is rich in 9‐cis, 11‐trans, 13‐cis conjugated linolenic acid, decreased the accumulated hepatic triacylglycerol in Otsuka Long‐Evans Tokushima Fatty (OLETF) rats, and administration of 2 mL kg −1 day −1 pomegranate seed oil significantly improved insulin sensitivity in type 2 diabetic animals . This effect is probably due to the large differences in many aspects, such as physiological structure and metabolism between animals and humans, but it also lays a foundation for future clinical research involving pomegranate.…”
Section: Effects Of Pomegranate On T2dmmentioning
confidence: 99%